1998
DOI: 10.1083/jcb.142.4.1053
|View full text |Cite
|
Sign up to set email alerts
|

The Ras Target AF-6 is a Substrate of the Fam Deubiquitinating Enzyme

Abstract: The Ras target AF-6 has been shown to serve as one of the peripheral components of cell–cell adhesions, and is thought to participate in cell–cell adhesion regulation downstream of Ras. We here purified an AF-6-interacting protein with a molecular mass of ∼220 kD (p220) to investigate the function of AF-6 at cell–cell adhesions. The peptide sequences of p220 were identical to the amino acid sequences of mouse Fam. Fam is homologous to a deubiquitinating enzyme in Drosophila, the product of the fat facets gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 48 publications
3
98
0
Order By: Relevance
“…Immunoblot experiments using the testicular and ovarian extracts clearly demonstrated that anti-Af-6 and anti-Usp9x Ab specifically recognized a specific single band of approximately 205 and 220 kDa respectively. These data clearly confirmed the high specificity of each Ab as was demonstrated in previous studies (Taya et al 1998, Kanai-Azuma et al 2000. PMSG treatment revealed an enhancement of Usp9x expression level, slightly in the testes and strongly in the ovaries (right-hand plates in Fig.…”
Section: Localization Of Af-6 and Usp9x In Sertoli Cellssupporting
confidence: 76%
See 2 more Smart Citations
“…Immunoblot experiments using the testicular and ovarian extracts clearly demonstrated that anti-Af-6 and anti-Usp9x Ab specifically recognized a specific single band of approximately 205 and 220 kDa respectively. These data clearly confirmed the high specificity of each Ab as was demonstrated in previous studies (Taya et al 1998, Kanai-Azuma et al 2000. PMSG treatment revealed an enhancement of Usp9x expression level, slightly in the testes and strongly in the ovaries (right-hand plates in Fig.…”
Section: Localization Of Af-6 and Usp9x In Sertoli Cellssupporting
confidence: 76%
“…As well as the post-translational regulation of tight and adherens junction proteins, a gap junction protein, Connexin43, is also degraded via the ubiquitin proteasome pathway (Laing & Beyer 1995, Laing et al 1997. Moreover, our previous report (Taya et al 1998) showed a possible regulation of Af-6, an integral component of tight and adherens junctions, by an Usp9x-mediated ubiquitin pathway. These studies therefore clearly indicate that the balance between positive and negative regulators of ubiquitylation may likely be involved in the junction dynamics in various epithelial cells, including Sertoli and granulosa cells of mammalian gonads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A and B). Among the putative ERG-binding proteins (SI Appendix, Table S1) identified by both pulldown and immunoprecipitation was a deubiquitinase enzyme, USP9X (15). We validated the physical interaction of ERG with USP9X by immunoblot analysis of coimmunoprecipitation with endogenous ERG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has two splice variants, l-afadin and s-afadin, but only the larger splice variant (l-afadin) can bind to actin (Mandai et al, 1997). s-Afadin (also known as AF-6), on the other hand, can localize to both the plasma membrane and nucleus (Buchert et al, 2007) and has also been reported to form a complex with and serve as a substrate for Fam [a deubiquitinating enzyme (Taya et al, 1998)]. This implies that proteolytic degradation of AF-6 occurs via the ubiquitin-proteasome pathway.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%